THE LEADERSHIP MODEL OF THE LORD JESUS: TRANSFORMATIVE LEADERS - Vinus Zai; Junianus Zega (Sekolah Tinggi Teologi Excelsius, 2023)
The Lord Jesus Leadership Model in the sense of transformative leaders is a leadership model that should be emulated by world leaders because it is idealized influence, inspiration, intellectual stimulation and individualized consideration. The Lord Jesus' Leadership Model in the sense of transformative leaders brings change in terms of: 1. Transformative Faith and Trust, 2. Transformative Social 3. Transformative Ministry. Ideally, leadership that should be an example for world leaders and church organizations is the leadership model of the Lord Jesus: Transformative leaders who are leaders of leaders.Tulisan ini memiliki tujuan menganalisa tentang Model Kepemimpinan Tuhan Yesus dalam arti transformative leaders merupakan model kepemimpinan yang patut diteladani oleh para pemimpin hamba Tuhan di zaman ini. Model Kepemimpinan Tuhan Yesus diteliti dengan cara deskriptif kualitatif dan dianalisa dengan seksama. Ditemukan bahwa Model Kepemimpinan Tuhan Yesus sangat idealized influence, inspiration, intellectual stimulation dan individualized consideration. Model Kepemimpinan Tuhan Yesus dalam arti transformative leaders membawa perubahan dalam hal: 1. Faith and Trust Transformatif, 2. Social Transformatif 3. Ministry Transformatif. Idealnya kepemimpinan yang patut menjadi teladan bagi para memimpin dunia dan organisasi gereja adala model kepemimpinan Tuhan Yesus: Transformatif leaders yang adalah leader of leaders